Some Provisions In The 1945 Constitution Of The Republic Of Indonesia Are Further Regulated By The Law - Yudi Widagdo Harimurti; Aprilina Pawestri; Farell Heydar Hilmy Fattuberty (Technium Social Sciences Journal, 2023)
The highest written legal basis in the unitary state of the Republic of Indonesia is the 1945 Constotution of the Republic of Indonesia. This means that some provisions in the 1945 Constitution of the Republic of Indonesia gelede normstelling need further regulation with laws and regulations. Given that the product of state law is the Constitution and laws and regulations, it is correct and appropriate if some provisions in the Constitution are further regulated by laws and regulations. The laws and regulations, as stipulated in the 1945 Constitution of the Republikc of Indonesia are Law, Perpu, PP, Perpres, Perda.